2012
DOI: 10.5539/ep.v2n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polycyclic Aromatic Hydrocarbons on Sexual Maturity of Atlantic Cod, Gadus morhua, following Chronic Exposure

Abstract: Mature Atlantic cod, Gadus morhua, were exposed in an ambient flow-through sea water system to low concentrations of water-accommodated fractions (WAFs) of a crude oil for periods of 38-92 days to ascertain its effects on sexual maturity. Some exposed groups were depurated after exposure for 4 to 287 days. Minimal mortality but a greater percentage of skin and gill lesions and a reduction in weight gained, especially in females, occurred in the WAF-exposed cod in contrast to controls in summer-autumn. The WAFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Our data bolster the growing body of evidence that hydrocarbon exposure can alter egg production in female fish (Brown‐Peterson et al ; Perrichon et al ; Raimondo et al ) and decrease reproductive fitness in male fish by reducing fertilization rate (Booc et al ). Hydrocarbons have also been shown to reduce sperm quantity (Sundt and Bjorkblom ) and quality (Nagler and Cyr ) and delay spermiation (Khan ), though those endpoints were not assessed in the present study. Correlation analyses revealed that tissue concentrations of parent and alkyl PAHs were negatively correlated with both egg production and fertilization rate, providing additional supportive evidence that the changes observed in egg production and fertilization rate in the present study are a result of hydrocarbon exposure and not natural variation between tanks.…”
Section: Discussionmentioning
confidence: 89%
“…Our data bolster the growing body of evidence that hydrocarbon exposure can alter egg production in female fish (Brown‐Peterson et al ; Perrichon et al ; Raimondo et al ) and decrease reproductive fitness in male fish by reducing fertilization rate (Booc et al ). Hydrocarbons have also been shown to reduce sperm quantity (Sundt and Bjorkblom ) and quality (Nagler and Cyr ) and delay spermiation (Khan ), though those endpoints were not assessed in the present study. Correlation analyses revealed that tissue concentrations of parent and alkyl PAHs were negatively correlated with both egg production and fertilization rate, providing additional supportive evidence that the changes observed in egg production and fertilization rate in the present study are a result of hydrocarbon exposure and not natural variation between tanks.…”
Section: Discussionmentioning
confidence: 89%
“…We have previously demonstrated that exposure to crude oil highenergy water accommodated fraction (HEWAF; an environmentally relevant PAH mixture), results in reduced egg production by SHM and developmental effects in two generations of offspring (Jasperse et al, 2019). Many other studies have also reported reproductive impairment in fish exposed to PAHs, including reduced egg production (Brown-Peterson et al, 2013;Raimondo et al, 2016;Vignet et al, 2016), reduced serum estradiol levels (Pollino et al, 2009) delayed spawning and spermiation (Khan, 2012), and altered testicular development (Sundt and Bjorkblom, 2011). However, it remains unknown how adverse environmental conditions common to estuarine environments affect the sensitivity of SHM to the reproductive effects of HEWAF.…”
Section: Introductionmentioning
confidence: 99%
“…The observed effects in fish include reduced levels of reproductive hormones (estrogens and androgens), inhibited gonadal growth, appearance of a female egg protein (vitellogenin; VTG) in male fish blood; gonadal histopathology and even intersex fish containing testis-ova or ovotestes resulted in decline in fish populations which has been observed in many parts of the world (Jobling et al, 2002, Keiter et al, 2006and Khan, 2013.…”
Section: Introductionmentioning
confidence: 99%